Strategies for the Integration and Development of Taiwan's Sports and Cultural Tourism Industry: A Study Based on the RMP Theory (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Strategies for the Integration and Development of Taiwan's Sports and Cultural Tourism Industry: A Study Based on the RMP Theory